Innovation Potential of Kazakhstan’s Regions: Evaluation and Ways For Development - Mukhtаrovа, K.; Myltykbayeva, A. (Farabi Journal of Social Sciences, 2016)
The paper aims to evaluate innovation potential of regions in the Republic of Kazakhstan and propose ways for its development.Despite the fact that regional innovation systems in Kazakhstan have been formally established for more than 10 years, there are a lot of unsolved problems and lack of understanding in this field. This defines the urgency of identifying real innovation potential of regions in our country with following attempts to find solutions.